Optimization of Chicken Egg Distribution Cost Using Revised ASM Method (Case Study: Breeding Industry) - Devani, Vera; Rahmadani, Chlarisya (Jurnal Teknologi, 2024)
PT. IA is a company engaged in the manufacture of animal feed, producing chicken eggs and broiler chicken farm. The problems at PT. IA is amount of distribution costs incurred by the company, so the method needed to optimize disttribution costs. The purpose of this research is to determine the optimal distribution costs of chicken eggs, compare the distribution cost of chicken eggs before and after optimization, and compare the ASM method with Stepping Stone method. The method use to solve the probelum is using ASM method. ASM method is one of a method that can use to find the optimal solution without have to find the starting solution to minimize costs. Allocation product with ASM Method is done from the smallest index and the largest amount of supply, until all demand is met and supply out of stock.  Based on the research, it shown the revision of ASM method is not necessarly able to provide the optimal solution directly to unbalanced transportation problems or the accurance of additional activities. The minimum total cost with ASM method is Rp. 586.800.000, while after test the optimization using Stepping Stone method the result is Rp. 585.300.000. The difference cost before and after optimization using the revised ASM method is Rp. 93.300.000 or decrease of 13.7%.